Adverse Childhood Experiences and Co-Occurring Disorders: Is There a Relationship Among ACEs, Mental Health Issues, and Substance Use Among Inmates? - Crick, Skylar N. (Journal of drug issues, 2024)
Previous literature has shown that adverse childhood experiences (ACEs) are a factor in future criminal behavior, victimization, and overall health. Research has also found that co-occurring disorders (CODs) are prevalent among inmates with approximately half of inmates meeting the criteria of mental health and substance use disorders in previous studies. Exposure to ACEs and drug use may also be higher in rural, Appalachian areas with the opioid crisis impacting adults and children alike. Moreover, research has indicated that some relationships, such as parenthood, may serve as protective factors for those involved in the justice system. The current study explores the relationship between ACEs and CODs, specifically in the areas of substance use and mental health among a rural jail sample. This study utilizes an Inmate History and Needs interview survey completed by 166 inmates (59 females, 107 males) from three different rural jails in a southern state to examine the relationship between ACEs and CODs among inmates, if CODs differ among male and female inmates, and the relationship between parents, CODs, and living with their children prior to arrest. We found that inmates in our study report high rates of ACEs, mental health issues, and drug use, and there is a significant relationship between exposure to ACEs and CODs.